Adjustment function as a tool for distribution of seats in the European Parliament - Misztal, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The article points out the concept of degressive proportionality, which is defined in the Lisbon Treaty and concerns allotment of seats in the European Parliament. The article introduces the concept of adjustment functions that allows the execution of the transition from the proportional division to degressively proportional. It reminds us of the four methods based on adjustment functions leading to degressively proportional divisions in the weak sense. Methods that are listed are: "shifted proportionality" (by Pukelsheim), parabolic method (by Ramirez), power-type method (by Ramirez), and power-type method (by Haman). The article contains a proposition of a special form of an adjustment function, which is dependent on an increasing, strictly concave function and several parameters. These are the population of the least and most populous country of the European Union (now Malta and Germany), the minimum and maximum number of seats to be allocated (now 6 and 96) and the additional parameter c. It is chosen in such a way that, with a fixed method of rounding of the adjustment function (and thus calculating the number of seats per country), the total number of seats does not exceed a certain fixed value (target 750).
Mathematical Economics, 2011, Nr 7 (14), s. 137-154
Keywords: degressive proportionality; European Parliament; the adjustment function; the Lisbon Treaty